Effectiveness of Strengthening Exercises for the Elderly with Low Back Pain to Improve Symptoms and Functions: A Systematic Review - Nor Azizah Ishak; Zarina Zahari; Maria Justine (Scientifica)
Objective. To determine the effect of strengthening exercises for older people with low back pain (LBP). Methods. This study is a systematic review of experimental study which evaluated the evidence regarding exercises for older people with LBP by using EBSCO Academic Search Premier, EBSCO EconLit, Science Direct, PUBMED, and PEDro from 2006 to 2016. Search strategy for each database was conducted by using keywords such as “low back pain”, “older people”, and “strengthening exercise”. Boolean operators were used to combine keywords and manual exclusion was conducted to verify studies which met the inclusion criteria. The articles reviewed were evaluated and critically appraised by using PEDro scale and SPSS version 20 was used to analyze the data. Results. Three articles were found regarding strengthening exercise for older people with LBP whereas one study was conducted on multicomponent exercise. The mean, standard deviation, and variance of the PEDro score of all the studies were 5.67, 2.33, and 1.528, respectively. Overall, the qualities of all studies reviewed were fair. Two articles showed significant results when compared to control group (p<0.05). Conclusions. Strengthening exercise is a beneficial treatment for older people with LBP in reducing pain intensity, disability, and improved functional performances.